An Empirical Study on The Impact of Host Countries’ Environmental Regulations on Chinese OFDI - Fang, Chen (Transactions on Economics, Business and Management Research, 2024)
With the widespread adoption of green and low-carbon development concepts globally, economic growth has also been imbued with more elements of green development. Thus, the environment protection factors take more and more important role in the evaluation system of foreign investments all around the world, which raise the question of whether and how the escalating environmental regulations of host countries can affect Outward FDI (OFDI). Using a uniquely merged dataset of Chinese firm-level OFDI and country-level environmental regulations data over the sample period 2009–2019, this paper investigates the impact of host countries’ environmental regulations on Chinese OFDI from both host countries’ and multinational enterprises’ perspectives, and adds evidence from developing countries with weaker regulations to the ’pollution haven theory’.The conclusions show that Chinese multinational corporations are easily attracted by lax environmental regulations in alternative countries when choosing overseas locations, while strict environmental regulations in host countries reduce the investment probability of Chinese multinational corporations . Overall, the ’pollution haven effect’ exists in the process of Chinese enterprises’ overseas investment location choice, and several robustness checks confirm our findings. Heterogeneous tests indicate that non-OECD countries are more likely to become pollution havens than OECD countries who have more stringent environmental regulations. Mechanism analysis indicates that the natural resource rent of each country could moderate the impact of host countries’ environmental regulations on Chinese OFDI. Implications for both policy and managerial decision-making are also discussed.